Metastases to the thyroid gland from renal cancer. Issue 3 (May 2013) - Cesaretti, Manuela; Trotta, Manuela; Varaldo, Emanuela; Ansaldo, Gianluca; Leale, Irene; Borgonovo, Giacomo
Aims and background: Metastases to the thyroid gland from renal cancer pose a challenge to physicians, due in part to the rarity of the phenomenon, the prolonged time interval between removal of the primary renal cancer and the appearance of metastases, the difficulty in diagnosis, and the uncertainty regarding long-term prognosis. We report our experience with diagnosis and management of patients affected by thyroid metastases from renal clear cell carcinoma. Study design: We report herein three clinical cases of thyroid metastases from renal clear cell carcinoma. We also present a review of the literature and examine common features of clinical presentation and management recommendations. Results: Over the past 17 years, 918 patients underewent surgery for thyroid cancer in our institution. Histological examination demonstrated a thyroid secondary malignancy from kidney cancer in 3 cases. Two patients underwent total thyroidectomy, whereas in the third patient a palliative right lobectomy with homolateral latero-cervical lymphoadenectomy was performed. At a 5-year follow-up, only one patient survived and was disease-free. Conclusions: Thyroid metastases from renal clear cell carcinoma are a rare occurrence but should be taken into consideration in the differential diagnosis of a thyroid nodule. Preoperative diagnosis is often difficult. Nevertheless, an extensive diagnostic workup is recommended because the subsequent therapy must be tailored on the basis of the local extension of metastases. Surgical treatment of solitary thyroid metastases is recommended. However, patients with disseminated disease have a poor prognosis, and palliative care is the indicated recommendation. In these patients and in surgically untreatable patients, prolonged survival may be achieved by adjuvant medical therapy.